A pathology order interface based on the transmission of texts obtained from pathology requisitions and just-in-time construction of HL7 messages - Jay J. Ye; Derek K. Higgins; Barry L. Evans (Elsevier, 2022)
Background: A pathology order interface using Health Level 7 standards (HL7) generally has an HL7 client program that gathers information from the clinical electronic medical record system, packages the information in the form of HL7 message, and sends the message using secure communication protocols to an HL7 interface engine located on the pathology side. We describe an alternative approach that transmits the texts obtained from requisitions, with subsequent just-in-time construction of HL7 messages. Materials and methods: The order interface is between a dermatology clinic EMR and pathology information system. A text acquisition and processing program runs in the background in desktop computers in dermatology clinic so that a copy of pathology requisition text is obtained each time when the clinic prints a pathology requisition. Discrete elements of the data are extracted from this text, prepended to the text and saved on a shared drive within the dermatology office intranet. This text file is then transferred to pathology intranet using secure File Transfer Protocol (sFTP). Once received, an HL7 message construction program extracts the discrete data elements to construct an HL7 message. The HL7 message is then forwarded to an HL7 interface engine and entered into the pathology information system as an order. Results: Using an actual case as an example, the content and format of the information flowing through different steps of the interface are demonstrated. Conclusions: The construction of such an interface does not involve the clinic EMR vendor, thus avoiding its associated cost and potential delay. This interface has advantages over our other order interfaces constructed using the conventional approach in that it does not require a change of order process and it avoids duplicate orders.